To solve this expression, you would follow the order of operations, which is PEMDAS (parentheses, exponents, multiplication and division from left to right, addition and subtraction from left to right). In this case, you would first perform the multiplication before the division. So, 4 divided by 4 is 1, and 1 multiplied by 6 is 6. Therefore, the answer to 4 over 4 times 6 is 6.
Chat with our AI personalities
4/6=x/24 96=6x 16=x
1/6*24 = 4
"2 over 3x equals 4" is an equation in a single variable, x.2/(3x) = 4 => 3x/2 = 1/4 => 3x = 2/4 = 1/2 => x = 1/6.
6^4=1296
(x/4) - 4 = (3x/4) - 6 The first step to solving this equation is to multiply the entire equation by 4 to eliminate the denominators under x. Doing so yields the equation: x - 16 = 3x - 24 Simply combining like-terms will yield 2x = 8 So x is equal to 4